If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -17x = 4 + 3x Solving 8 + -17x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 8 + -17x + -3x = 4 + 3x + -3x Combine like terms: -17x + -3x = -20x 8 + -20x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 8 + -20x = 4 + 0 8 + -20x = 4 Add '-8' to each side of the equation. 8 + -8 + -20x = 4 + -8 Combine like terms: 8 + -8 = 0 0 + -20x = 4 + -8 -20x = 4 + -8 Combine like terms: 4 + -8 = -4 -20x = -4 Divide each side by '-20'. x = 0.2 Simplifying x = 0.2
| 3(2k+11)=2(12+3k) | | k+5/12k/5k-3/4k | | 15-(3x+1)=4(x+1)+3x | | 3/4=-x/16 | | (3w+5)(3-w)=0 | | (4n^2+4n-1)4= | | 45=-9/4x | | -5(3y-5)-y=-4(y-4) | | -8=6+2x | | a-9=-22 | | m-64.9=-30.3 | | w=32w | | -22=-313+x | | 4(-5x+3)=6x+4 | | X-(3/4)(2x-12)=7x/2+5 | | 26x+3=5(5x+8) | | 56=-2(21-m)+4(m-4) | | -17=x-36 | | T=0.6(205-18/2-144)+144 | | 0.40=ln(y) | | 6(4x-7)-4=6(x-4)+104 | | 3x-2-5x=x+2+x | | 16p^4-4p^2=0 | | 6/5+2/5x=29/10+5/2x+1/2 | | 9x-8x=19fory | | 2(x-5)+10=-(-3x+2) | | 5(3x-7)-8=5(x-3)+22 | | 11y+15x=-23 | | 7x+n=5 | | 10=11x | | 5(-7x-5)-4x=2 | | (7c-5)(8c+4)= |